Efektifitas dan efisiensi realisasi anggaran belanja: studi kasus di BAPPEDA Kabupaten Temanggung - Sugiharti, Rr. Retno; Jumaroh, Jumaroh (Journal of Economics Research and Policy Studies, 2021)
Implementing activities or programs in public sector organizations is required to pay attention to the concept of effectiveness and efficiency. The BAPPEDA of Temanggung Regency as one of the public sector units also applies this principle in implementing activities in its environment. Of the units under the Temanggung Regency government, the Temanggung Regency BAPPEDA has the highest budget compared to other OPDs. Therefore, this study aims to analyze the effectiveness and efficiency of implementing the BAPPEDA budget of the Temanggung Regency. Using the descriptive analysis method, the results of the analysis can be seen that the level of effectiveness and efficiency in the period 2014 -2020 shows varying values. The highest level of effectiveness occurred in 2015 and the lowest occurred in 2016. Implementing expenditure planning for 2014-2020 can be categorized as effective because the programs implemented have been realized. Implementing the 2014-2020 budget, in terms of efficiency, is classified as very efficient. From these results, it can be concluded that the Temanggung Regency BAPPEDA is considered to have carried out budget management very well where the budget management at the Temanggung Regency BAPPEDA is under the concept of effectiveness and efficiency.